Pemamfaatan logam sisa permesinan pada knalpot guna mengurangi pencemaran udara - Siregar, A.M.; Siregar, C.A.; Affandi, A. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2021)
Exhaust gas emissions from motorized vehicles also contribute to air pollution in our environment. So it is necessary to reduce air pollution so that the negative impacts on humans, animals and the environment can be reduced. Hoping and making alternative tools to reduce exhaust gas in 100cc motorcycle vehicles. With experimental methods and testing of 100cc motor vehicle exhaust emissions with a comparison of standard exhaust data. Tests are carried out on the exhaust to determine the results of exhaust gas emissions, plus a modified exhaust with the addition of scrap ST-40 iron. The elements to be observed are the CO value, HC value and CO2 value as comparative data. The tool that will be used to store and view these elements is the Gas Analyzer. This tool is a useful tool for measuring the portion and composition of combined gases. From the results of testing and analysis, it is obtained exhaust gas emission testing data with an average engine speed of 500 rpm, and exhaust pipe temperature of 400C to 450C. After the standard exhaust model, then the exhaust model. In tests that added 50 g, 70 g, and 90 g of ST-40 iron, it was found that the best way to reduce and reduce exhaust emissions was an exhaust with added pieces of ST-40 90 g iron. And when compared to standard exhaust, CO element drops to 72.35% and HC element drops to 58.70%. and the element CO2 decreased to 74.28%.